Spatiotemporal patterns of influenza incidence changes in mainland China, 2004–2020 - Tao, Shengcong; Guo, Yirong (Frontiers in Public Health, 2025)
BackgroundInfluenza incidence varies significantly over time and across regions. However, the current understanding of the spatiotemporal patterns of influenza incidence changes in mainland China is limited, which significantly hampers the relevant authorities' ability to prevent and control influenza outbreaks.ObjectivesThis study aims to update and enhance the understanding of influenza incidence patterns in China through a large-scale spatial and temporal analysis of cases among a population of ~1.4 billion, providing a reference for planning and optimizing prevention and treatment strategies.MethodsMonthly surveillance data on influenza incidence across all provinces of mainland China from 2004 to 2020 were collected, and the intra-annual distribution characteristics were statistically summarized. An exponential trend model was used to estimate inter-annual trends on monthly, quarterly, and annual scales for each province, and their spatial patterns were explored and analyzed. The spatial heterogeneity was examined using linear regression models.ResultsThe average annual incidence of influenza in mainland China from 2004 to 2020 was 31.57 cases per 100,000 people, with significant outbreaks occurring in 2009 and 2019, exceeding the expected values by 142% and 323%, respectively. It reveals clear regional differences, with a higher prevalence in the east and a lower prevalence in the west, indicating localized clustering. The intra-annual distribution pattern follows a U-shaped curve, characterized by a high incidence in winter and a low incidence in summer. The monthly, seasonal, and annual influenza incidence showed an overall increasing trend, with a more pronounced rise after 2010, particularly reflected in the increased number of cases during winter months. The trend varies by geographic location, showing a significant negative correlation with elevation and a significant positive correlation with longitude. Provinces with larger populations experience greater fluctuations and faster growth.ConclusionsThe influenza prevention and control situation in mainland China remains severe. Macro-level strategies should account for these temporal and spatial patterns, allocate limited medical resources effectively, and respond actively and promptly to potential outbreaks in key regions and at critical times.